2010
DOI: 10.1128/aem.01446-10
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-Resistant Escherichia coli Bacteria, Including Strains with Genes Encoding the Extended-Spectrum Beta-Lactamase and QnrS, in Waterbirds on the Baltic Sea Coast of Poland

Abstract: Individual cloacal swabs of mallards (Anas) to isolate fluoroquinolone-resistant E. coli. PCR was used to detect specific antibiotic resistance genes. We found 9 E. coli isolates producing ESBL with bla genes: bla CTX-M-1 (6 isolates), bla CTX-M-9 plus bla TEM-1b (1 isolate), bla CTX-M-15 plus bla OXA-1 (1 isolate), and bla SHV-12 (1 isolate). In the isolate with bla CTX-M-15 , the gene aac(6)-Ib-cr was also detected. The bla genes were harbored by transferable plasmids of the IncN and IncI1 groups. Nine quino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
116
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(134 citation statements)
references
References 82 publications
14
116
3
1
Order By: Relevance
“…In recent years, different reports have alerted us to the spread of VRE and/or ESBL-containing E. coli isolates from clinical, farm and wild animals in different European countries (Mallon et al, 2002;Torres et al, 2003;Bonnedahl et al, 2010;Literak et al, 2010;Pinto et al, 2010). Although the percentage of vanA isolates from wild birds in the Azores was lower when compared with other studies performed in mainland Portugal in farm and wild animals (Poeta et al, 2005a;Gonçalves et al, 2010;Radhouani et al, 2010b, Radhouani et al, 2010c, our isolates showed a phenotype of multi-resistance.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…In recent years, different reports have alerted us to the spread of VRE and/or ESBL-containing E. coli isolates from clinical, farm and wild animals in different European countries (Mallon et al, 2002;Torres et al, 2003;Bonnedahl et al, 2010;Literak et al, 2010;Pinto et al, 2010). Although the percentage of vanA isolates from wild birds in the Azores was lower when compared with other studies performed in mainland Portugal in farm and wild animals (Poeta et al, 2005a;Gonçalves et al, 2010;Radhouani et al, 2010b, Radhouani et al, 2010c, our isolates showed a phenotype of multi-resistance.…”
Section: Discussioncontrasting
confidence: 46%
“…In this study, the ESBLcontaining E. coli isolate, classified in the A phylogroup, was more sensitive to the antimicrobial compounds tested than ESBL-positive E. coli isolates recovered from other wild animals in mainland Portugal Poeta et al, 2009;Pinto et al, 2010;Radhouani et al, 2010a). Moreover, the b-lactamase genes detected in our isolate (bla CTX-M-14 and bla SHV-12 ) were also found in wild birds in Sweden (Bonnedahl et al, 2010) and Poland (Literak et al, 2010). How these wild birds acquired VRE and ESBL-containing E. coli is unclear.…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, it is of general public interest to keep the number of coliform in the environment as low as possible. The E. coli strains isolated from the European population of P. carbo have not only been shown to be highly resistant to antibiotics such as cephalosporins and fluoroquinolones but the highly virulent O25b-ST131 clone has been identified among them (Literak et al, 2010;Tausova et al, 2012). Altogether, these findings indicate that cormorants may spread epidemiologically important antimicrobial-resistant bacteria through their droppings.…”
Section: Role In Pathogen Dispersionsupporting
confidence: 51%
“…FQ and ESC resistant E. coli strains have been identified in wild birds (Allen et al, 2010;Literak et al, 2010) and from Australian wildlife rehabilitation centres (Blyton et al, 2015). Chapter 4 of this thesis identified wild birds as a potential risk factor associated with increased APEC carriage in healthy birds.…”
Section: Investigating the Prevalence Of Carriage Of Avian Pathogenicmentioning
confidence: 99%